Water management and sustainability in Asia - Alias, Nor Eliza; Haniffah, Mohd Ridza Mohd; Sobri Harun (Community, environment and disaster risk management, 2021)
Water is life. Managing water quantity and quality is a big part of human responsibility. Water Management and Sustainability in Asia covers topics related to water resources management, including multi- and interdisciplinary research on flood, soil infiltration, contaminants, sediment, water quality, hydrological modelling, and water resources systems. Presenting case-studies on soil infiltration and contaminants, the impacts of flood with risk assessment, as well as water modelling and management systems. The lessons shared in this volume focus on rapidly developing countries in the South-east Asia who have a complex climate system which presents challenges. This research provides models and projections that can support water management in the region.